PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INKUIRI TERBIMBING BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATERI LUAS BANGUN DATAR PADA SISWA KELAS VI SD NEGERI WONOKERSO 01 - Kuswanto; Agus Sutono; Joko Siswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The problem in this study is that teachers are less skilled at developing syllabuses, lesson plans and media. The purpose of this study was to determine the validity, practicality, and effectiveness of learning tools with the Local Wisdom-Based Guided Inquiry Model which were developed to Improve Problem Solving Ability on Flat Area Material in Grade VI Students. This research is a development research according to Borg & Gall. The instruments developed were syllabus, lesson plans, student books and worksheets. The results of this study are that the developed learning tools have gone through a validation process and have been declared valid by experts in their field with slight revisions and are categorized as good. The use of local wisdom-based Guided Inquiry learning model learning tools is declared practical. The learning of the material on the Flat Shape Area by using learning tools of the Local Wisdom-Based Guided Inquiry Learning Model was declared effective. Keywords: Inquiry training, local wisdom, problem solving ability